PENGEMBANGAN MEDIA PEMBELAJARAN BIOLOGI BERBASIS FLASH PADA SUBMATERI STRUKTUR DAN REPLIKASI VIRUS KELAS X - Hendry, Yerianus; Yeni, Laili Fitri; Marlina, Reni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractIn the globalization era, the education and technology has a significant development.Conventional learning system felt less able to involved and improve studentmotivation. This research aims to produce flash-based biology learning media was aviable to use, and knowing student responses to flash-based biology learning media onthe sub material characteristic, structure, and virus replication. This research was thedevelopment research consisting of two stages: preliminary stage (preparation anddesign) and formative evaluation stage (self evaluation, expert reviews, small groupevaluation, and field test). The data collection instrument was a validationquestionnaire, and student responses questionnaire. Validation of flash-based biologylearning media was doing by 6 validator consist of 3 media experts, and 3 materialexperts. Learning media was have valid categorized on the result of the validation bymedia experts with 3,76 and material experts with 3,74. While student responses washave very positive with student responses percentage 88,47%. So the conclude wasflash-based biology learning media fit for use as a learning media. Keywords: Flash-Based Biology Learning Media, Development Research, Characteristic, Structure, and Virus ReplicationÂ